EVALUASI PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE MATERIAL REQUIREMENT PLANNING PADA HOME INDUSTRYSARANA BERSIH “LIMA” - Sugeng Pramono (Manajemen Bisnis, 2014)
The purpose of this study is to determine the results of Raw Material Inventory Control evaluation with Material Requirement Planning method in May 2014, so the company Home Industry Sarana Bersih " Lima "can minimize inventory costs. Analysis tool used is a method of inventory control with materials requirement planning (MRP) engineering approach. MRP method is a mathematical method or technique that is used to assist managers in making decisions regarding the amount of inventory, production planning schedule, the schedule ordering, and inventory costs. Based on the analysis by using the method of Material Requirement Planning it can be seen that the results of the cost incurred by the company on the stock in May is 1.220.000 rupiah. There are savings of 293.400 rupiah of the total cost of 1.513.400 rupiah.Keywords: Inventory, Inventory control, Material Requirement Planning.